2019
DOI: 10.17219/acem/99613
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of the aryl hydrocarbon receptor (AhR) and estrogen receptor (ER) in the developing teeth of rat offspring after rat mothers’ exposure to 2,3,7,8-tetrachlorodib

Abstract: expression of the aryl hydrocarbon receptor and estrogen receptor in the developing teeth of rat offspring after rat mothers' exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin and the protective action of α-tocopherol and acetylsalicylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…These effects have been revealed in archaeological bone material. 50 Other studies showed that the use of a-tocopherol in high doses for a period of 3 weeks following the administration of TCDD contributed to a signicant reduction in IL-6 and TNF and also protected collagen against degradation. 3 The administration of ASA for a period of 3 weeks following the application of TCDD was aimed at reducing the inammatory reaction induced by the stimulation of COX-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been revealed in archaeological bone material. 50 Other studies showed that the use of a-tocopherol in high doses for a period of 3 weeks following the administration of TCDD contributed to a signicant reduction in IL-6 and TNF and also protected collagen against degradation. 3 The administration of ASA for a period of 3 weeks following the application of TCDD was aimed at reducing the inammatory reaction induced by the stimulation of COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…The TCDD, a-tocopherol and ASA doses were determined based on previously published data. 50 Aer a period of 3 weeks following administration of TCDD in the individual groups (FTCDD, FTCDD + E, FTCDD + ASA), the above-mentioned groups and the FC group were mated with males that had not been treated with any chemicals. Aer a period of 7 days aer mating, pregnant females were placed in separate cages.…”
Section: Division Of Animalsmentioning
confidence: 99%
“…Several factors can disturb tooth formation [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. They include biological (genetic, developmental, viruses, bacteria, cancer), physical or chemical factors.…”
Section: Discussionmentioning
confidence: 99%
“…The liver plays a significant role in inflammatory response, directly affecting the synthesis of acute-phase proteins and the transformation of steroid hormones such as cortisol, estrogens, and testosterone [ 1 , 2 , 3 ]. It has been proven that there are many factors that affect the ultrastructure of hepatic cells, causing disorders of their secretory function which in turn affects the concentration of acute-phase proteins and the electrophoretic distribution of plasma proteins.…”
Section: Introductionmentioning
confidence: 99%